Empathetic Relationships Through Emotional Literacy in Early Childhood - Lailatul Badriyah; darmaji dwi cahya; Weliani Pebrianti; Jeli Fikasari (EMPATI: Jurnal Bimbingan dan Konseling, 2026)
Abstract.This study aims to examine the relationship between empathy and emotional literacy in early childhood. The research employed a quantitative method with a correlational approach. The sample consisted of 16 children aged 3-6 years, selected through purposive sampling. Data were collected using validated and reliable empathy and emotional literacy scales. Pearson correlation analysis revealed no significant relationship between empathy and emotional literacy in early childhood (r = 0.291, p > 0.274), as young children have not fully developed an understanding of empathy toward others. These findings suggest that children's emotional literacy is not solely dependent on empathy but is influenced by other factors. Young children can recognize others' emotional states without necessarily engaging in empathetic responses. This study provides insights for educators and parents in designing learning programs aimed at enhancing children's emotional literacy. Keywords: empathy, emotional literacy, early childhood, correlational study